2020
DOI: 10.1111/cei.13510
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae lipids license TLR-4 for activation of NLRP3 inflammasome and autophagy to evoke a proinflammatory response

Abstract: TLR4 is usually not assumed to be involved in Mycoplasma recognition. In this study we showed that the Mycoplasma pneumoniae‐derived lipids did interact with TLR4 which subsequently initiates the activation of NLRP3 inflammasome and formation of a positive feedback loop between autophagy and NF‐κB signalling cascade, ultimately promoting proinflammatory cytokines production in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
0
31
1
1
Order By: Relevance
“…Psoriasis is an autoimmune chronic skin disease characterized by hyperproliferation of keratinocytes [ 1 ]. The amplification of dendritic cells and T-cells from the immune system releases various proinflammatory cytokines and chemokines with simultaneous activation of growth factors together involve in the pathogenesis of psoriasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is an autoimmune chronic skin disease characterized by hyperproliferation of keratinocytes [ 1 ]. The amplification of dendritic cells and T-cells from the immune system releases various proinflammatory cytokines and chemokines with simultaneous activation of growth factors together involve in the pathogenesis of psoriasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“… 34 Additionally, MP can activate the production of cellular tumor necrosis factor-α, a cytokine that both triggers and maintains the inflammatory response. 35 Moreover, mucus cell hypersecretion and goblet cell hyperplasia have been observed in the airways of MP - infected mice. 36 …”
Section: Discussionmentioning
confidence: 99%
“…34 Additionally, MP can activate the production of cellular tumor necrosis factor-a, a cytokine that both triggers and maintains the inflammatory response. 35 Moreover, mucus cell hypersecretion and goblet cell hyperplasia have been observed in the airways of MPinfected mice. 36 Interestingly, in this study, the significantly different MP DNA load at enrollment between patients with refractory and non-refractory MPP 21 indicated that the MP DNA load is a risk factor of refractory MPP because of the direct injury caused by an increased MP load.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our current understanding of their biological effects is limited, hence lipids might possibly be TLR4 ligands. Our recent data also demonstrate that high concentrations of lipids could trigger the secretion of proinflammatory cytokines in mouse macrophages via TLR4 [305]. Owing to the biochemical particularity of lipids, it is difficult to study their functions through gene knockout as done in vivo and in vitro, hence resulting in fewer lipids being functionally characterized.…”
Section: Future Perspectivesmentioning
confidence: 95%